THE INFLUENCE OF PROMOTION IN DECISION-MAKING TO BECOME A HAJJ SAVINGS CUSTOMER AT BANK SYARIAH INDONESIA KCP PANGKALAN BRANDAN - Sri Wahyuni; Khairani Sakdiah; Nova Arma Dwi (CV. Barokah Publsiher, 2026)
The development of Islamic banking in Indonesia has shown significant growth in line with the increasing awareness of the Muslim community in utilizing Sharia-based financial products. One of the superior products offered by Islamic banks is Hajj Savings, which functions as a financial planning instrument to carry out the Hajj. The public's decision to become a customer of Hajj savings is influenced by several factors, one of which is promotion. Promotion plays an important role in conveying information, building understanding, and forming a positive perception of hajj savings products offered by Islamic banks. This study aims to analyze the influence of promotion on the decision to become a hajj savings customer at Bank Syariah Indonesia (BSI) KCP Pangkalan Brandan. This study uses a quantitative approach using an associative method. The population consists of all hajj savings customers at BSI KCP Pangkalan Brandan, with a sample of 80 respondents selected through purposive sampling. Data were collected using questionnaires based on the Likert scale and analyzed through validity tests, reliability tests, classical assumption tests, and simple linear regression analysis using SPSS. The results of the study show that promotions have a positive and significant effect on the decision to become a Hajj savings customer. Therefore, an effective and sustainable promotion strategy is very important to increase public interest in choosing hajj savings products at BSI KCP Pangkalan Brandan.